044 Impact of the role of a physician in charge of pane management in the emergency room of a university hospital. (23rd September 2015) - Lecomte, F; Koné, V; Ginsburg, C; Pourriat, J L; Claessens, Y E; Vidal-Trécan, G
Abstract : Background and objectives: 70% to 80% of patients visiting an emergency department (ED) complain from pain. In 1999 a survey to the ED of a university hospital found that only a quarter of patients were relieved on discharge. We implemented and evaluated a program aiming at improving the management of pain in the ED. Programme: A physician of the ED was appointed to lead the drafting of protocols by a multidisciplinary group of professionals and provide staff training. It was decided that the nurses on arrival using a validated scale would assess the pain. In case of pain, the priority sorting would be increased by a level. Moderate pain would be immediately treated using an analgesic stage 1 acting quickly and other measures (immobilisation) would be implemented if appropriate. Two cross-sectional surveys were conducted (04 October 1999–19 October 1999 and 03 April 2007–18 April 2007). The information was collected using a structured questionnaire in all patients over 17 years able to answer questions. Pain and its intensity were assessed on arrival and on discharge by a validated scale. A structured form enabled file analysis. Intervention was defined as every measure intended at pain relieving and pain relief as the disappearance of pain on discharge or a decrease in its intensity. The effectiveness of the program was assessed by the change in the proportion of patients relieved on discharge. Results: 810 and 745 patients were eligible in 1999 and 2007, respectively. On 726 (90%) and 673 (90%) participants, 563 (77%) and 536 (80%) were painful on arrival, among them, 384 (68%) and 401 (75%) had their pain assessed on discharge. The proportions of patients relieved were 44% in 2007 vs 25% in 1999 (p<0.0001). The proportions of patients receiving an intervention, respectively, before and during the medical examination were 63% and 82% vs 14% and 36% (p<0.0001). Pain recorded in file was found in 97% cases vs 74% (p<0.0001), and its intensity was evaluated on arrival in 96% cases vs 26% (p<0.0001), a validated scale was used in 90 % of cases vs 73% (p<0.0001). Pain was reassessed in 14% cases vs 4.5% (p<0.0001). The treatment was adjusted in 11% vs 4.8% (p<0.0001). The program seems independently associated with pain relief: patients visiting in 2007 were 2.3 times (95% CI 1.2 to 4.3) more likely to be alleviated than patients visiting in1999. Vital emergency, intensity of pain, analgesic intake prior to arrival and intervention on arrival are also independently related to pain relief. Discussion and Conclusion: Further progress is necessary since 56% of patients are still not relieved on discharge, including support for those whose symptoms seem less severe. A specific emphasis should be placed on the reassessment of pain after treatment and adjustment of therapy. The type of survey used comparing before to after does not allow determining whether the program implemented determined the improvement or whether other changes may explain it. The facts that the interventions on pain at the reception, sorting level are related to relief and that the program is mainly applied are in favour of the impact of this program. Monitoring indicators will track the impact of changes. The program established under the direction of a dedicated physician has had a positive impact on the management of pain in an ED. Such program should be continued. Contexte et objectifs: La douleur touche 70 % à 80% des patients des Services d'accueil des urgences (SAU). En 1999, une enquête au SAU d'un hôpital universitaire a montré qu'un quart seulement des patients étaient soulagés à la sortie. Un programme ayant pour objectif l'amélioration de la prise en charge de la douleur dans ce SAU a été mis en place et évalué. Programme: Un médecin du SAU a été désigné pour mener la rédaction de protocoles par un groupe pluriprofessionnel et assurer la formation du personnel. Il a été décidé que la douleur serait évaluée par les infirmiers d'accueil et d'orientation par une échelle validée, qu'en cas de douleur intense, la priorité de tri serait augmentée d'un niveau, que pour les douleurs modérées, un antalgique de palier 1 d'action rapide serait immédiatement administré et d'autres mesures (immobilisation…) seraient prises si indiquées. Deux enquêtes transversales ont été effectuées (04/10/1999 - 19/10/1999 et 03/04/2007 – 18/04/2007). Les informations ont été recueillies à l'aide d'un questionnaire structuré chez tous les patients de plus 17 ans capables de répondre aux questions. L'existence d'une douleur et son intensité ont été évaluées à l'arrivée et à la sortie par une échelle validée. Une grille structurée a permis l'analyse des dossiers. Sont appelés « intervention » les mesures antalgiques et « soulagement », une absence de douleur à la sortie ou une diminution de son intensité. Le critère principal de jugement de l'efficacité du programme est l'évolution de la proportion de patients soulagés à la sortie. Résultats: Respectivement, en 1999 et 2007, 810 et 745 patients étaient éligibles ; sur les 726 (90%) et 673 (90%) participants, 563 (77%) et 536 (80%) étaient douloureux à l'entrée ; parmi eux, 384 (68%) et 401 (75%) avaient eu leur douleur évaluée à la sortie. La proportion de patients soulagés était de 44% en 2007 vs. 25% en 1999 (p<0.0001). Les patients ont bénéficié de l'intervention respectivement avant et pendant l'examen médical chez 63% et 82% vs 14% et 36% (p<0.0001). La douleur était mentionnée dans le dossier dans 97% des cas vs 74% (p<0.0001) ; son intensité avait été évaluée à l'entrée dans 96% des cas vs 26% (p<0.0001), par une échelle validée dans 90% des cas vs 73% (p<0.0001). Elle avait été réévaluée dans 14% des cas vs 4, 5% (p<0.0001).Le traitement avait été ajusté dans 11% vs 4, 8% (p<0.0001). L'exécution du programme semble indépendamment lié au soulagement des patients : les patients de 2007 avaient 2, 3 fois (IC 95% : 1, 2 – 4, 3) plus de chance d'être soulagés que ceux de 1999. L'urgence vitale, l'intensité de la douleur, la prise d'antalgique avant l'arrivée et l'intervention dès l'accueil sont aussi indépendamment liées au soulagement. Discussion et conclusion: Des progrès restent à faire puisque 56% des patients ne sont toujours pas soulagés à la sortie, notamment une prise en charge accentuée de ceux dont les symptômes semblent moins graves. L'accent doit aussi être mis sur la réévaluation de la douleur après traitement et l'ajustement du traitement. Le type d'enquête utilisé comparant l'avant et l'après ne permet pas d'identifier si seule l'application du programme a déterminé l'amélioration ou si d'autres évolutions peuvent l'expliquer. Le fait que l'intervention sur la douleur dès l'accueil, le niveau de tri soient liés au soulagement et que le programme soit majoritairement appliqué sont en faveur de l'impact de ce programme. Le suivi d'indicateurs permettra de suivre l'impact des modifications apportées. Le programme mis en place sous la direction d'un médecin dédié, a eu un impact favorable sur la prise en charge de la douleur dans un SAU. Il sera poursuivi.